THE ISSUES AND CHALLENGES OF TEACHING ENGLISH AS A SECOND LANGUAGE IN WESTERN AUSTRALIA: A FOCUS ON STUDENTS WITH AFRICAN REFUGEE BACKGROUNDS - Oliver, Rhonda; Mbano, Noah (Nova Science Publishers, 2015)
Self-identity is an issue for many African refugee background (ARB) students. They battle with retaining aspects of their =Africaness‘ in a changed environment, whilst working to accept and fit into a new culture. At the same time, however, they may feel a sense of disloyalty to their place of origin and to their parents. Although many of the participants described in this chapter continue to struggle with their identities, they also reported that they had made a conscious decision to conform to the new culture as a way to facilitate a positive stay in Australia and to improve their English proficiency. They described that they were doing this by adopting new identities, even taking on new Western names, and that these measures helped them to feel safer and more comfortable at school. To explore these issues which are presenting challenges for Australian ESL teachers, this chapter will discuss, firstly, self-identity and identity crisis, then religious and cultural identities, and thirdly, the burden of being black and how this sometimes manifests as a reluctance to succeed.